ANALISIS PENGGUNAAN PREFIKS PADA KALIMAT SISWA TUNAGRAHITA KELAS XI SKHN 1 KOTA SERANG DENGAN STIMULUS MEDIA GAMBAR - Ulinnuha Ulinnuha; Rina Andriani; Desma Yuliadi Saputra (Prakata: Jurnal Bahasa dan Sastra Indonesia Serta Pembelajaran, 2024)
The purpose of this study was to describe (1) the prefix form used by mentally retarded students in class XI SKhN 1 Serang (2) the prefix function used by mentally retarded students in class XI SKhN 1 Serang (3) the meaning of the prefix used by mentally retarded students in class XI SKhN 1 Serang. The method used in this study is a qualitative method with a descriptive approach. This study involved two levels of mental retardation, namely moderate and mild. The data collection techniques used in this research are literature study, documentation, and assignments. Based on the analysis that has been carried out, the use of prefix forms in words in sentences using image media stimuli, mentally retarded students in class XI SKhN 1 Serang, for students with moderate mental retardation with IQ = 36-52, tend to change the form, function and meaning of prefixes. me with the prefix be-., while people with mild mental retardation with an IQ level of = 52-67, are able to use the form, function, and meaning of the prefix in accordance with existing rules. It is necessary to provide special teaching materials for prefix material for mentally retarded students in class XI SKhN 1 Serang